The Impact of Force Production on Initial Acceleration Interacting with Block Start Obliquities (American Journal of Innovation in Science and Engineering, 2023)
This study aimed to improve the block starts initial acceleration performance for 100m athletes. In this research, to have faster block starts, athletes will need to work on starting block position and improve acceleration out of the blocks by using the most suitable block Pendle obliquities. Aim to investigate the during athlete block clearance force production effect on different obliquities in 100m performance in sprinters Initial Acceleration (IA) (0-10 m) Phase. Identify the most accurate block Pendle notches for block clearance performance for using force plate on foot paddles. According to the sample sprinter (n=8) collected data from using Qualisys 3D Motion Capture Analysis Software and Data Analysis through SPSS Statistics (version 27.0). This research employed one group post-test only design to improve acceleration through block start clearance performance force production of 100m sprinters. As supposed, accurate block start obliquities influence the Minimize time in the block clearance performance. Further, Athlete acceleration time also has decreased. That acceleration phase time increment supports the achievement of their personal best timing in 100m events.